Programme outcomes attainment towards psychomotor skill development during open distance learning in engineering laboratory courses / Prof. Ir. Dr. Che Maznah Mat Isa ... [et al.] - Mat Isa, Che Maznah; Tahir, Wardah; Oh, Chai Lian; Noh, Narita; Chiew, Fei Ha; Tukiar, Mohd Azuan; Mohd Noor, Nur Asmaliza; Rumambo Pandin, Moses Glorino (Universiti Teknologi MARA, Kedah, 2024)
Open distance learning (ODL) has faced an enduring challenge in delivering programs associated with psychomotor skills caused by the COVID-19 pandemic. The teaching, learning, and assessment related to psychomotor development during ODL have often been less effective than traditional methods due to the absence of technical skills like hands-on equipment handling, which are challenging to implement in remote learning environments. This paper focuses on attaining programme outcomes or graduate attributes related to developing psychomotor skills in laboratory courses during ODL within the context of engineering education. A quantitative research approach was used to gather insights, using a questionnaire survey administered to engineering students engaged in laboratory courses via ODL. The findings revealed that engineering students perceive three significant program outcomes attained during ODL, which were the ability to determine the correct methods and procedures, including experiment design, the capacity to synthesise information to devise practical solutions for challenging issues, and the ability to propose valid conclusions and solutions for given problems. However, it is crucial to note that the ability to collect data accurately, primarily through tool usage, remains a fundamental psychomotor skill ranked as the least attained programme outcome during ODL. This highlights the unique challenges faced when teaching and assessing practical skills in remote environments. Furthermore, the study showed that using engineering laboratories during ODL was perceived as the least effective method for addressing psychomotor skill development. These findings suggest the need for innovative strategies and technology-enabled solutions to bridge the gap between theoretical knowledge and hands-on practice in engineering education during ODL. It also demonstrates the urgent requirement to enhance the delivery of practical skills in ODL, particularly within engineering laboratory courses. Further research should focus on innovative methodologies for remote psychomotor skill development, such as virtual labs and simulation technologies, to provide a more comprehensive and practical learning experience for engineering students engaged in these programs.